Impact of environment, culture, and sports tourism on the economy: a mediation-moderation model - Sonia Lohana, Sonia Lohana; Muhammad Imran, Muhammad Imran; Ahmed Harouache, Ahmed Harouache; Aysha Sadia, Aysha Sadia; Zahoor Ur Rehman, Zahoor Ur Rehman (Taylor & francis, 2023)
The aim of this study is to investigate the direct relationship between the environment, culture, sports tourism and economy. Additionally, in this study, we have used sports tourism as a mediating variable in the relationship between environment, culture, and economy. Moreover, the moderating role of the destination image in the proposed relationships is examined. To validate the model, data obtained from 373 Malaysian Ministry of Tourism, Arts, and Culture employees is incorporated into structural equation modeling (SEM), PLS 4. According to the findings of this study, there is a positive and significant relationship between the environment, culture, sports tourism and the economy. Additionally, sports tourism mediates the relationship between the environment, culture, and a country’s economy. Interestingly, the study also found that destination image does not moderate the relationship between sports tourism and the economy. Overall, these findings highlight the importance of a healthy and culturally rich environment and the potential benefits of sports tourism for the economy. The findings of this research have important implications for policymakers and can be helpfully used in the tourism industry. In practical implications, fostering a healthy environment, preserving cultural heritage, and promoting sports tourism and destination image can boost the country’s economy